Assessing the Computer Literacy Level of Distance Education Students in Ghana - Arkorful, Valentina; Anhwere Barfi, Kwaku; Kafui Aheto, Simon-Peter; Ayensu, Eunice (Ghana Library Journal, 2025)
The concept of computer literacy in distance education or learning continues to be an integral area of research due to the importance of digital literacy in the academic performance of distance learners. The study examined the level of computer literacy among distance education students in Ghana. Differences in the level of computer literacy based on area of residence and gender among the distance learners were also examined. The study adopted quantitative analysis with a cross-sectional survey design. The study used a census-based method to choose its participants. Out of the 4236 undergraduate level 400 or final year students adopted for the study, 3003 responded using the link on the class WhatsApp platform. The level 400 undergraduate students were selected because the researchers assumed they would be aware of their computer literacy levels due to the number of years they have spent and engaged in the university. The findings revealed that there was a generally low level of computer literacy skills among the participants. It was further revealed that there was no significant difference between males and females in their level of computer literacy. However, there were differences in their level of computer literacy based on area of residence, where urban settlers were found to have higher computer literacy than rural settlers. It was recommended that distance education administrators apply a multifaceted approach to enhance skills in digital communication, data privacy, information literacy and software application in distance education. It could be achieved through providing training and support for both students and educators, integrating digital literacy into the curriculum, and fostering a supportive online learning environment that encourages collaboration.